Ethnomedicine for stomach ache by the tribes of Srikakulam district, Andhra Pradesh - Ramarao Naidu, B.V.A.; T.V.V. Seetharami Reddi (Journal of Traditional and Folk Practices (JTFP), 2017)
The paper deals with 31 species of plants covering 31 genera from 23 families used by the Savara, Jatapu, Konda dora, Gadaba, Kuttiya and Yerukula tribes of Srikakulam district, Andhra Pradesh for curing stomach ache. Family-wise analysis showed that the dominance of Rubiaceae with 4 species followed by Sterculiaceae, Fabaceae, Asteraceae, Asclepiadaceae, Acanthaceae (each 2) and others. Herbs are dominant with 12 species followed by trees (9), shrubs (8) and others. Root is used in 13 practices followed by leaf (7), stem bark (5) and others. 7 practices were found to be new or less known. The study is undertaken since there are no such ones in the region.